Pemanfaatan Blended Learning dalam Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah 1 Tepus, Gunung Kidul, D.I. Yogyakarta - Riswanda Riswanda; Affandiya Ramadhani; Farras Hilmy Taukhid Izzudiin; Ahmad Alan Alfian; Alfi Mahyudi Awali (MAN 4 Kota Pekanbaru, 2026)
Developments in 21st-century education demand learning innovations that integrate technology without sacrificing essential values, including in Islamic Religious Education (PAI) learning. One relevant model is blended learning (BL), a combination of face-to-face and online learning. This study aims to describe the implementation of BL in Islamic Religious Education (PAI) learning at Muhammadiyah 1 Junior High School, Tepus, Gunung Kidul, and identify supporting factors, obstacles, and its impact on student motivation and learning independence. This study used a qualitative descriptive approach with a case study through observation, interviews, and documentation with the principal, PAI teachers, and eighth-grade students. Data analysis was conducted using the Miles and Huberman model with triangulation of sources and techniques. The results indicate that BL was implemented quite effectively and adaptively, increasing student motivation and learning independence and making PAI learning more varied and contextual. However, obstacles remain, including limited internet access, devices, and students’ digital literacy. Overall, BL has the potential to be an effective and relevant PAI learning model in the digital era, particularly in religious-based schools in remote areas.